Resolving sub-cycle signatures: A perspective on hallmarks of terahertz metrology - Benea-Chelmus, Ileana-Cristina; Tomasino, Alessandro (Frontiers in Photonics, 2023)
Frequency up-conversion has become amongst the most prevalent techniques for detection of terahertz waves in metrology systems. State-of-the-art up-conversion techniques rely on the coherent transferring of the information encoded in all degrees of freedom of a terahertz wave to either the near-infrared or visible domain, where detectors are readily accessible. This allows for an indirect reconstruction of the terahertz wave. However, unlike most up-conversion methods employed in photonics which are concentrating on narrowband tones (at both terahertz and near-infrared frequencies), a broadband, hence temporally constrained, terahertz transient is sampled on time-scales shorter than its oscillation period. Here, femtosecond laser pules serve as temporal gates. In this perspective, we highlight several hallmarks of terahertz metrology that originate from these sub-cycle measurement capabilities and elaborate why this enables studies in fundamental and applied science, with a particular focus on novel measurement concepts in classical and quantum. We focus on so-far demonstrated detection performance in bulk nonlinear crystals. Finally, we discuss current challenges and the most pressing questions ahead.